Factors associated with effective coverage of child health services in Burkina Faso - Koulidiati, Jean-Louis; De Allegri, Manuela; Souares-Coutant, Aurélia; Brenner, Stephan (Tropical medicine & international health, 2018)
To identify factors associated with both crude and effective health service coverage of under-fives in rural Burkina Faso.